Are Barranquilla and Atlantico prepared to face competitiveness challenges? - Ariza Osorio, Yesid (Corporación Universitaria Americana, 2013)
El presente artículo reflexivo, pretende una mirada a la situacio?n de la Regio?n Caribe, en especial el departamento del Atla?ntico y su capital, en relacio?n con los retos en materia de competitividad a los que se enfrenta de acuerdo a los diferentes Tratados de Libre Comercio con Estados Unidos, Corea del Sur, Suiza y la Comunidad Europea. Presenta una mirada a la economi?a atlanticense y un acercamiento a la inquietud sobre el cumpli- miento de los retos que se han planteado por diversos estudios de sectores y centros de investigacio?n del pai?s. Palabras clave: Competitividad, Atla?ntico, Oportunidades comerciales, Retos competitivos, Regio?n Caribe. ABSTRACT This paper focuses on a reflection about on the competitive conditions of the Colombian Caribbean Region to face the challenges of the Free Trade Agreements that Colombian government has signed with the United States, South Korea, Switzerland and the European Community.An economic analysis is shown so that you can obtain a comprehensive view over the whole fulfillment of the goals proposed by research institutes at the point time when they were negotiating FTAs with foreign countries. Keywords: Competitiveness, Atlantico, Business opportunities, Competitive challenges, Caribbean Region.